Correlation of Severe Lumbar Spondylosis with Sociodemographics of Patients with Chronic Low Back Pain - Terkimbi Annongu; Msuega Chia; Tornyor Aligba; Ojaare Magaji (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: Once red flag diagnoses such as cancer and fracture are ruled out in patients with chronic low back pain (CLBP), lumbar spondylosis (LS) tops the differential diagnosis. Various sociodemographic factors are associated with LS. The study aims to explore the presence and extent of LS in association with the various sociodemographic factors of CLBP.Material and methods: This was a prospective hospital-based study. Lumbosacral radiographs of patients investigated for CLBP related to the various sociodemographic factors were evaluated for presence and severity of LS, graded using Kellgren-Lawrence grading of LS.Results: Sixty-two males and 61 females (M: F of 1.0:1.1) aged 16-80 years with a clinical history of CLBP were studied. Fifty- seven patients (46.4%) had mild LS (≤KL2), 10 (8.1%) moderate (KL3), and 23(18.7%) severe (KL4). Thirty -three (26.8%) cases were normal (KL0). Females had more normal radiographs; males had mostly moderate-severe radiographs. LS was rare below 20 years; after that, the frequency increased and was highest at 21-50 years. Those with no formal education had the severest forms of LS and were statically significant (p=0.000). Moderate-severe forms of LS were commoner in individuals with high BMI and were statically significant (p=0.000). Farmers had the most severe forms of LS and demonstrated the highest total sum of all cases of LS and was statically significant (p=0.000).Conclusions: Severe forms of lumbar spondylosis are associated with various socio-demographics. Smoking, however, seems to have a protective effect on the development of severe LS; this, however, needs further exploration.